2021
DOI: 10.30979/revabeno.v21i1.1663
|View full text |Cite
|
Sign up to set email alerts
|

Uso de serviços odontológicos por escolares do sul do Brasil e fatores associados

Abstract: Este estudo transversal teve por objetivo avaliar a prevalência e os fatores associados ao uso de serviços odontológicos pelos escolares de 12 anos no município de Santa Cruz do Sul (RS), sul do Brasil, por meio de uma ação que integrou ensino e serviço. Examinadores previamente treinados e calibrados realizaram os exames clínicos e um questionário referente às características demográficas, socioeconômicas e comportamentais foi respondido pelos escolares. Modelos em multinível de regressão de Poisson foram uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This finding is in agreement with a study conducted in Brazil among 12-year-old schoolchildren that showed that brushing teeth more than two times a day was associated with a greater probability of dental services utilization. 17 In the aforementioned study, which did not include children with ASC, toothbrushing was associated with self-esteem and self-care. These factors also contributed to a greater use of dental services.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in agreement with a study conducted in Brazil among 12-year-old schoolchildren that showed that brushing teeth more than two times a day was associated with a greater probability of dental services utilization. 17 In the aforementioned study, which did not include children with ASC, toothbrushing was associated with self-esteem and self-care. These factors also contributed to a greater use of dental services.…”
Section: Discussionmentioning
confidence: 93%